V. Lenin’s Ideas – Landmarks of our Work (The Review of the Interinstitutional Scientific Conference of Philosophers) - Pulkauninkas, Stasys (Problemos, 1970)
The paper surveys the materials of the interinstitutional conference of philosophers, devoted to the Lenin Centenary, which took place on the 18th of April, 1970, in Vilnius Kapsukas State University. The author states the base ideas of the reports, particularly of those that are not printed in this issue of the magazine. The thorough analysis of the proletariat leader’s heritage was the principle task of the conference, determining the problems discussed: the structure and functions of the system of the proletariat dictatorship, the principles of aesthetical evolution in the works of V. I. Lenin, the Leninist logical ideas and the development of modern logics, V. I. Lenin’s views and theoretical generalizations on the place of Marxism In the history of philosophy, the constructive character of cognition, etc.